2009
DOI: 10.1016/j.ejcts.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of video-assisted limited surgery for early lung cancer☆

Abstract: The present intervention study showed that thoracoscopic-limited surgery for clinically early lung cancers depending on findings in preoperative HRCT is feasible and appropriate from the viewpoint of oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…1) of which 81 fit the inclusion and exclusion criteria. Among the 81 articles, 11 articles did not report on PSNs [19, 2130], 2 did not include surgically resected cases [31, 32], 13 did not report DFS, lung cancer-specific-survival, or overall survival [33–45], 9 articles reported only on recurrence/death [13, 4653], and 10 articles were conference abstracts with insufficient data. This left 36 articles reporting on 31 unique studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) of which 81 fit the inclusion and exclusion criteria. Among the 81 articles, 11 articles did not report on PSNs [19, 2130], 2 did not include surgically resected cases [31, 32], 13 did not report DFS, lung cancer-specific-survival, or overall survival [33–45], 9 articles reported only on recurrence/death [13, 4653], and 10 articles were conference abstracts with insufficient data. This left 36 articles reporting on 31 unique studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Distinguishing between PSNs and solid nodules with only one CT scan may be difficult, particularly for solid nodules as they may be surrounded by a thin rim of haziness (i.e., nonsolid component). Thus, when progression from an NSN to PSN or solid nodule cannot be confirmed on thin-section CT scans; upper limits of the solid component of PSNs should be used to avoid misclassifying a solid nodule as a PSN [4, 5, 19, 20]. Examples of such misclassifications have been reported, leading to misunderstanding of the cell types that manifest as PSNs and their survival rates [5].…”
Section: Methodsmentioning
confidence: 99%
“…The pooled HR of OS/CSS from studies published after 2004 was 1.255 (95% CI: 1.100–1.431, P = 0.001) (Supplementary ). The combined HR of RFS from 15 eligible studies was 1.325 (95% CI: 1.019–1.724, P = 0.036) (Supplementary ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, sublobar resection has shown equivalent oncological results and survival outcome compared with lobectomy (25)(26)(27). Moreover, in 2010, Sugi and colleagues reported a retrospective study of 159 patients, revealing that there were no significant differences among the wedge resection, segmentectomy, and lobectomy approaches in the treatment of small NSCLC (28). Therefore, a limited resection is considered more appropriate in specific patients, such as those with small lung lesions, elderly patients, or those at a high risk of comorbidity.…”
Section: Discussionmentioning
confidence: 99%